Pengaruh Jenis Media Tanam dan Interval Pemberian Pupuk Daun Terhadap Pertumbuhan Plantlet Anggrek Dendrobium Blue Twist x Dendrobium Biggibum pada Tahap Aklimatisasi dan Pembesaran - Pretty Aulia Dewi Fortuna; Sismanto Sismanto; Desi Maulida; Lisa Erfa; Ratih Rahhutami; Rahmadyah Hamiranti (Politeknik Negeri Lampung, 2023)
Dendrobium orchids have the potential to be developed because they have a variety of types, shapes and sizes. The choice of planting media and fertilization is an important factor in the success of orchid propagation, especially at the acclimatization stage. The aim of this research were determine the type of planting media and the best interval for giving foliar fertilizer and determine the best interactions and combinations of treatment of the type of planting media and the interval for giving foliar fertilizer on the growth of dendrobium orchid plantlets in the acclimatization and enlargement stages. This research used a factorial Randomized Block Design (RAK) with the first factor being the type of planting media and the second factor being the interval of foliar fertilizer application. The first factor includes M1: wood charcoal, M2: cocopeat, M3: wood charcoal + cocopeat 1:1, M4: wood charcoal + cocopeat 1:2, and M5: wood charcoal + cocopeat 1:3. The second factor includes P1: once every 4 days, P2: once every 8 days, P3: once every 12 days. The results of the research showed that the cocopeat planting media type provided the best percentage of acclimatization success for the Dendrobium Blue twist x Dendrobium Biggibum orchids. Providing foliar fertilizer at 8-day intervals provides the best increase in plantlet height and leaf width at the acclimatization and plantlet enlargement stages of Dendrobium Blue twist x Dendrobium bigibbum orchids. There was no interaction between the use of planting media type and the interval of foliar fertilizer application.